Koinōnia and the Psychology of Possession - Konrádová, Veronika (Pontificia Universidad Católica del Perú. Departamento de Humanidades, 2022)
This paper addresses the concept of koinōnia discussed in Plato’s Republic. It focuses on the specific ways the term enters the discussion about social organisation within the guardian class, such as the proposal for abolishing a nuclear family in favour of the community of wives and children. The paper aims to reveal the psychological basis connecting Plato’s socio-economic proposals to his principal ethical and political concerns. It examines (i) the argument supporting the proposals of the social organisation of the guardians, (ii) the psychological background of these proposals, (iii) the socio-cultural context against which these proposals are defined and (iv) the position of these considerations in the broader scheme of Plato’s thought.

Este trabajo aborda el concepto de koinōnía discutido en la República de Platón. Se enfoca en las formas específicas en las que el término se introduce en la discusión sobre la organización social al interior de la clase de los guardianes, tal como la propuesta de abolir la familia nuclear a favor de la comunidad de esposas e hijos. Este artículo pretende revelar la base psicológica que conecta las propuestas socioeconómicas de Platón con sus preocupaciones éticas y políticas. Se examinará (i) el argumento que sustenta las propuestas de la organización social de los guardianes, (ii) el trasfondo psicológico de dichas propuestas, (iii) el contexto sociocultural frente al cual estas se definen y (iv) el lugar que ocupan estas consideraciones en el marco más amplio del pensamiento platónico.
Keywords: Koinōnia; Plato; The Republic; Possession; Psychology; Soul; Koinōnia; Platón; La República; Posesión; Psicología; Alma; https://purl.org/pe-repo/ocde/ford#6.03.01